#TITLE_ALTERNATIVE# - MULYANTO (NIM 13204231), BUDI
Limitation in human vision becomes an obstacle in identifying several objects or physical phenomenons. Every object naturally emits infrared spectrum with specific radiation peak and wavelength. This spectrum can be detected by infrared detectors, such as bolometer in which its resistance varies due to the amount of infrared radiation imposed on its surface. Bolometer is formed as an array and its output in the form of voltage information is collected by Read-Out Integrated Circuit (ROIC). The Final project deals with the design and implementation of the pixel selector circuit in Read Out Integrated Circuit (ROIC) for thermal camera. Pixel selector selects one out of 160 columns to be activated and one out of 120 pixels in that column to get the information from using MOS as analog switch. Analog signal will be slightly distorted because of charge injection and clock feedthrough and offset will be occurred. The first step of this project is to do theoretical calculation of the circuits and to simulate it with S-Edit in schematic circuit form. Technology used in this project is 0.5 μm (lambda 0.25 μm), single-poly and double-metal. Model SPICE used is BSIM3v3.2.4 from MIMOS. Layout of digital circuit is drawn automatically by L-Edit's Standard cell Place and Route (SPR) while layout of analog circuit is drawn manually. This layout is extracted and simulated again to verify the performance of the circuit compared to the specifications. Glitch occures in pixel selector's digital circuit's output and error voltage due to charge injection and clock feedthrough is almost same between after layout simulation (334 μV) and before layout simulation (312 μV). This result still fulfills the specified target.